The combined effect of tranilast 8% liposomal gel on the final cosmesis of acne scarring in patients concomitantly treated by isotretinoin: prospective, double‐blind, split‐face study. (8th August 2019) - Weinstein, A.; Koren, A.; Sprecher, E.; Zur, E.; Mehrabi, J. N.; Artzi, O.
Summary: Background: Tranilast [ N ‐(3, 4‐dimethoxycinnamoyl) anthranilic acid] has never been investigated for the prevention and treatment of acne scars. Aim: To evaluate the efficacy and safety of tranilast 8% gel in improving the final appearance of patients with acne scarring concomitantly treated by isotretinoin. Methods: This was a prospective, double‐blind, split‐face study, which enrolled 40 otherwise healthy participants (aged 18–49 years) with facial acne scars. For each patient, one half of the face were treated with tranilast 8% liposomal gel and the other half with a water‐based placebo. Using the Global Aesthetic Improvement Scale (GAIS), acne scars were evaluated by two dermatologists and by the patients, and the patients also rated their satisfaction with the treatment and reported adverse effects. Results: In total, 32 participants completed the trial. The mean GAIS scores at 5 months post‐treatment were significantly lower (better outcome) for the tranilast‐treated side than the placebo‐treated areas in patients concomitantly treated with isotretinoin ( P < 0.001). All the isotretinoin‐treated patients reported greater satisfaction and better general improvement in the skin's appearance and texture, and also greater improvement of pigment and redness on the tranilast 8% gel‐treated side compared with the control side. Conclusion: Combined topical application of tranilast 8% gel twice daily with oral isotretinoin treatment in the active phase of acne vulgaris may result in fewer scars, finer skin texture and enhanced appearance.